AB0511 The analysis of prognostic factors in patients with inflammatory myopathies and amyopathic dermatomiositis complicated with interstitial lung disease. (23rd January 2014) - Sugiyama, Y.; Hama, M.; Kishimoto, D.; Watanabe, R.; Yoshimi, R.; Ihata, A.; Ueda, A.; Takeno, M.; Ishigatsubo, Y.
Abstract : Background: Because interstitial lung disease (ILD) is one of the most critical manifestations and can be lethal in inflammatory myopathies (IM), especially amyopathic dermatomiositis (ADM), it is important to determine prognostic factors for survival. Objectives: We investigate clinical features which are associated with fatal events in IM patients having ILD. Methods: We retrospectively analyzed the association of clinical features, laboratory and HRCT findings, pulmonary function tests, and therapeutic regimens with clinical outcomes in 92 patients who were diagnosed with IM at our hospital from 1993 to 2012. Diagnoses of IM and clinical ADM were made according to Bohan and Peter criteria and modified Sontheimer's criteria, respectively. DM patients who did not met the ADM criteria were categorized as myopathic DM (MDM). The distribution and extent of ILD lesion were evaluated based on the percentage of the lung parenchyma involved in each of the four-divided lung zones from upper to lower, as previously described (1 ). Results: HRCT showed ILD lesions in 52 of 92 IM patients (56.5%); polymyositis (PM) 7, MDM 34, ADM 11. Routine malignant screening detected cancers in 11 (21%). Thirteen patients (25%) including 11 MDM and 2 ADM were died during follow-up period (median 33 months (1-229 months)) due to ILD (6 patients), infection (6 patients), and malignancy (4 patients). Nine were died within 7 months from the diagnosis. The levels of CK, CK/LDH ratio, and PCO2 before therapy were significantly lower in non-survivors than survivors (CK; 612±860 vs. 1920±2941, p=0.02, CK/LDH; 1.2±1.5 vs. 2.8±4.0, p=0.04, PCO2; 35.1±3.8 vs. 40.1±4.3, p=0.005). Particularly, lower PCO2 level than 38.9 mmHg was closely associated with poor survival prognosis (Figure, p=0.04). All of 6 patients who required mechanical ventilatory support died within 5 months, suggesting that hypocapnia predisposes to rapid progression of type I respiratory failure. No one died in 9 patients (17%) having positive anti-Jo-1 antibody. Although low DLco and higher ILD score in the upper lung fields had tendencies to be associated with unfavorable prognosis, the differences were not statically significant between survivors and non-survivors. Neither early therapeutic intervention nor intensive immunosuppressive therapies including steroid pulse, IVCY, and calcineurin inhibitors did not necessarily associate with favorable clinical outcomes in this series. Image/graph: Conclusions: The present study revealed that some MDM patients as well as ADM patients develop lethal ILD especially when relative ratio of CK to LDH was low and hypocapnia were found at the diagnosis. We need to establish multidisciplinary therapy including prophylactic procedures against infection more rapidly and intensively before type I respiratory failure progresses in IM associated ILD. References: Gunnarsson R, et al. Ann Rheum Dis. 2012;71(12):1966-72. Disclosure of Interest: None Declared